2011
DOI: 10.1016/j.marenvres.2011.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Source and profile of paralytic shellfish poisoning toxins in shellfish in Daya Bay, South China Sea

Abstract: 1Changes in cell density and cyst flux of Alexandrium tamarense, paralytic shellfish poisoning 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 25 publications
1
15
0
1
Order By: Relevance
“…catenella'' based on their morphological features (Qi and Tian, 1994;Anderson et al, 1996;Yu et al, 1998), though genetic studies have shown that both A. fundyense (Group I) and A. pacificum (Group IV) commonly occur (Wang and Hsieh, 2005;Tang et al, 2006;Gu et al, 2013a). Blooms of these species or PSTs have been reported in Dapeng Bay and Daya Bay of the South China Sea (SCS), coastal waters adjacent to the Changjiang River estuary in the East China Sea (ECS), and the northern Yellow Sea (YS) (Song et al, 2009;Wang and Wu, 2009;Wang et al, 2011). PSTs have also been detected in many bivalve samples collected along the coast of China (Anderson et al, 1996;Zhou et al, 1999;Wang and Wu, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…catenella'' based on their morphological features (Qi and Tian, 1994;Anderson et al, 1996;Yu et al, 1998), though genetic studies have shown that both A. fundyense (Group I) and A. pacificum (Group IV) commonly occur (Wang and Hsieh, 2005;Tang et al, 2006;Gu et al, 2013a). Blooms of these species or PSTs have been reported in Dapeng Bay and Daya Bay of the South China Sea (SCS), coastal waters adjacent to the Changjiang River estuary in the East China Sea (ECS), and the northern Yellow Sea (YS) (Song et al, 2009;Wang and Wu, 2009;Wang et al, 2011). PSTs have also been detected in many bivalve samples collected along the coast of China (Anderson et al, 1996;Zhou et al, 1999;Wang and Wu, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…have also been reported in the Yellow Sea, the coastal waters adjacent to the Changjiang River estuary and some bays in the South China Sea (Wang et al, 2006a(Wang et al, , 2011Song et al, 2009;Gu et al, 2013;Zou et al, 2014). Furthermore, A. tamarense blooms have been found to be associated with paralytic shellfish poisoning (PSP) toxin contamination in the cultivated shellfish in China (Wang et al, 2011;Chen et al, 2013;Jiang et al, 2013). The wide distribution of the species and their implication in harmful algal blooms (HABs) and PSP events have attracted increasing attention in China, and many studies have been performed on the nutritional characteristics, toxin composition, phylogenetics and toxicity of this genus (Chen et al, 1999;Yan et al, 2003;Wu et al, 2005;Fang et al, 2006;Tang et al, 2006;Gu et al, 2013;Jiang et al, 2013).…”
Section: Introductionmentioning
confidence: 75%
“…Blooms of toxic Alexandrium spp. have also been reported in the Yellow Sea, the coastal waters adjacent to the Changjiang River estuary and some bays in the South China Sea (Wang et al, 2006a(Wang et al, , 2011Song et al, 2009;Gu et al, 2013;Zou et al, 2014). Furthermore, A. tamarense blooms have been found to be associated with paralytic shellfish poisoning (PSP) toxin contamination in the cultivated shellfish in China (Wang et al, 2011;Chen et al, 2013;Jiang et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…2008;Wang et al 2011). to investigate the impact of algal toxins on the aquaculture area a solid phase adsorption toxin tracking (SPATT) method first developed by MacKenzie et al, (2004) was used here.…”
Section: Introductionmentioning
confidence: 99%